Tanjungjaya Village on the Rise: Integrating SWOT Analysis and Tourism Competitiveness for Sustainable Growth - Rifa Agustina Salsabila; Fauziah Eddyono (Ilomata International Journal of Social Science, 2026)
Village tourism development is increasingly recognized as a strategic approach to promoting sustainable tourism, enhancing local community welfare, and improving destination competitiveness. Tanjungjaya Tourism, located in the buffer zone of the Tanjung Lesung Special Economic Zone, possesses significant natural, cultural, and community-based potential, yet faces challenges related to technology integration, environmental management, and tourism governance. This study aims to analyze the competitiveness of Tanjungjaya Tourism and formulate development strategies using a SWOT framework that integrates competitiveness assessment with strategic planning.  A qualitative approach was employed through in-depth interviews with village leaders, Tourism Awareness Groups (Pokdarwis), local entrepreneurs, residents, and visitors, complemented by observation and documentation. Data were analyzed thematically using NVivo 15, with five dimensions of tourism competitiveness (economic, socio-cultural, political, technological, and environmental) operationalized as primary coding categories.  The findings reveal that the economic and socio-cultural dimensions are the most dominant, as evidenced by higher coding density, frequent recurrence across stakeholder groups, and strong triangulated thematic patterns. These dimensions are reflected in active community participation, the preservation of local cultural heritage, and the presence of tourism-related SMEs. However, key challenges remain, including limited technology integration, suboptimal policy implementation, and environmental management that requires more systematic planning.  The SWOT-based analysis identifies strategic priorities, including strengthening digital literacy, enhancing community-based governance, developing thematic tourism products, promoting ecotourism and cultural tourism, and integrating technology into destination management. This study provides a strategic framework to strengthen Tanjungjaya Tourism as a sustainable, community-centered destination and offers actionable pathways to enhance long-term competitiveness.